Seleksi Penerimaan Karyawan Baru Menggunakan Metode Multi-Objective Optimization On The Basis Of Ratio Analysis (MOORA) Dan Metode Multi Factor Evaluation Process (MFEP) - Feri Irawan; Elfi Fauziah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Companies/agencies can run and develop with the presence of workers or employees who have the ability according to the needs of the company/institution. In this case, the process of recruiting employees with various criteria and abilities is very necessary. The selection process is used to assess the ability of prospective employees so that qualified employees are obtained. To overcome this, the researchers designed and made a decision support system for the selection of new employees. The method used in this research is the Multi-Objective Optimization Method On The Basis Of Ratio Analysis (Moora) and the Multi Factor Evaluation Process (Mfep) method. This new employee acceptance decision support system program can be used as an alternative for agencies to assist and facilitate the decision-making process and provide solutions to the problems faced. The appraisal process is also faster and users are given the freedom to choose which prospective employees will be assessed.